Collaborative Governance in Environmental Protection and Management: Evidence From Lake Maninjau, Indonesia - Dewi Anggraini; Syaifuddin Islami; Mohd Azmir Mohd Nizah (Universitas Teuku Umar, 2026)
Environmental degradation in Lake Maninjau, West Sumatra, Indonesia, has become a complex governance challenge driven by the expansion of floating net cages (KJA), water pollution, and fragmented institutional coordination among stakeholders. Despite regulatory interventions and restoration programs, environmental management remains ineffective due to competing interests and weak coordination among government institutions, private actors, and local communities. This study analyzes the dynamics of collaborative governance in environmental protection and management in Lake Maninjau. This research employs a qualitative case study between August and November 2024. Data were collected through purposive sampling involving 11 key informants from local government institutions, private sector actors, and community groups. Data collection included in-depth interviews, field observations, and document analysis, which were analyzed using thematic analysis based on the collaborative governance framework proposed by Ansell and Gash. The findings show that collaborative governance develops through four interrelated dimensions: initial conditions shaped by ecological pressures and economic dependence on aquaculture; institutional design reflecting stakeholder roles in lake management; leadership exercised by the Agam Regency Government in coordinating initiatives; and collaborative processes developed through dialogue, trust building, and joint programs such as Save Maninjau. Strengthening institutional coordination, stakeholder participation, and regulatory enforcement is essential for sustainable lake governance.